Can the evaluation of marker placement confidence be used as an indicator of gait kinematic variability? - Fonseca, Mickael; Gasparutto, Xavier; Lena, Carcreff; Grouvel, Gautier; Bonnefoy-Mazure, Alice; Dumas, Raphaël; Armand, Stéphane (Frontiers in Rehabilitation Sciences, 2023)
Three-dimensional gait analysis is widely used for the clinical assessment of movement disorders. However, measurement error reduces the reliability of kinematic data and consequently assessment of gait deviations. The identification of high variability is associated with low reliability and those parameters should be ignored or excluded from gait data interpretation. Moreover, marker placement error has been demonstrated to be the biggest source of variability in gait analysis and may be affected by factors intrinsic to the evaluators such as the evaluator’s expertise which could be appraised through his/her experience and confidence in marker placement. In the present study, we hypothesized that confidence in marker placement is correlated with kinematic variability and could potentially be used as part of a score of reliability. Therefore, we have proposed a questionnaire to evaluate qualitatively the confidence of evaluators in lower-limb marker placement. The primary aim of this study was to evaluate the reliability and validity of the presented questionnaire. The secondary objective was to test a possible relationship between marker placement confidence and kinematics variability. To do so, test-retest gait data were acquired from two different experimental protocols. One protocol included data from a cohort of 32 pathological and 24 asymptomatic subjects where gait analysis was repeated three times, involving two evaluators. A second protocol included data from a cohort of 8 asymptomatic adults with gait analysis repeated 12 times, per participant, and involving four evaluators with a wider range of experience. Results demonstrated that the questionnaire proposed is valid and reliable to evaluate qualitatively the confidence of evaluators in placing markers. Indeed, confidence scores were correlated with the actual variability of marker placement and revealed the evaluator’s experience and the subjects’ characteristics. However, no correlation was observed between confidence scores and kinematic variability and the formulated hypothesis was not supported.